Affinity propagation‐based interference‐free clustering for wireless sensor networks. (8th December 2019) - Lin, Hai; Chen, Zhihong; Li, June
Summary: Wireless sensor networks (WSNs), eg, industrial WSNs, require reliability and real‐time communication. Clustering technique together with schedule‐based access can provide the benefits, such as energy saving, reliability, and timeliness. However, integrating above two technologies into WSNs requires sophistical time slot allocation mechanism. To simplify the time slot allocation, the paper proposes a distributed interference‐free clustering algorithm for WSNs. The algorithm is inspired by affinity propagation (AP) clustering algorithm. By adapting and improving the original AP algorithm, the proposed clustering algorithm aims to jointly optimize energy saving and coverage issues while providing interference free between clusters. The performance analysis demonstrates that it can achieve high receiving rate (reliability), low delay (real time), and low‐energy consumption. Abstract : By adapting and improving the original AP algorithm, the proposed clustering algorithm aims to jointly optimize energy‐saving and coverage problems while providing interference free between clusters.